Heart Failure with Preserved Ejection Fraction in the Indian Context - Rajeev Gupta; Mahesh Choudhary; Soneil Guptha (Journal of Indian College of Cardiology)
Heart failure with preserved ejection fraction (HFpEF) is defined as a clinical syndrome with current or prior symptoms or signs caused by a structural or functional abnormality with left ventricular EF ≥50%, corroborated by either elevated natriuretic peptides or objective evidence of cardiogenic pulmonary or systemic congestion diagnosed with imaging or hemodynamic measurements. In India, it is an underdiagnosed condition. Studies have reported that a third of patients with acute HF belong to this category. This review focuses on the diagnosis of HFpEF, including its pathophysiology, predisposing conditions, and mimics. Recent American College of Cardiology Expert Consensus Pathway and European Society of Cardiology guidelines have summarized current recommendations for its management. In these contexts, we discuss guideline-directed medical therapy with sodium-glucose cotransporter-2 inhibitors, mineralocorticoid receptor antagonists, angiotensin receptor–neprilysin inhibitors, angiotensin receptor blockers, and diuretics. Also highlighted are clinical care and referral pathways and novel approaches for management, including device therapies.